PELUANG BISNIS ANGKRINGAN DI KOTA PALANGKA RAYA - Hafizi, Muhammad Riza; Oktaviana, Nita (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2017)
The people of Palangka Raya city in today's modern era made angkringan as a place of social interaction and place of consumption for all social layers of society. Therefore the authors seen the existence of business opportunities angkringan. Angkringan was a place to buy food and drink